IMPLEMENTASI MODEL PEMBELAJARAN FLIPPED CLASSROOM PADA MATA PELAJARAN AL-QUR’AN HADITS di MTsN LIMAPULUHKOTA TAHUN PELAJARAN 2023/2024 - Elvia Agustina; Bambang Trisno; Anti Aina (ADIBA : JOURNAL OF EDUCATION, 2024)
The research focuses examined in this study are: 1) How is the implementation of the flipped classroom learning model in the subject of Al-Qur'an Hadith at MTsN 3 LimaPuluhKota in the 2023/2024 academic year? 2) How is the effectiveness of the implementation of the flipped classroom learning model in the subject of Al-Qur'an Hadith at MTsN 3 LimaPuluhKota in the academic year 2023/2024? The objectives of this study are: 1) describe the implementation of the flipped classroom learning model in the subject of Al-Qur'an Hadith at MTsN 3 LimaPuluhKota in the 2023/2024 academic year. 2) describe the effectiveness of the implementation of the flipped classroom learning model in the subject of Al-Qur'an Hadith at MTsN 3 LimaPuluhKota in the 2023/2024 academic year. This research uses a qualitative approach, with a type of case study research. While data collection techniques use interviews, observation, and documentation. Data analysis techniques used according to Miles Huberman's theory, namely: Data condensation, data presentation, and conclusion drawing. Data validity in this study uses source triangulation and technical triangulation. The results of this study are 1) the implementation of the flipped classroom learning model in the subject of Al-Qur'an Hadith at MTsN 3 LimaPuluhKota: students are asked to study the material at home first, students are asked to review the material that has been learned by raising their hands to scramble scores, students are told to memorize surah verses or hadith. The process of memorizing 2 to 3 times, then depositing the memorization. 2) Effective to motivate students to be active in learning. Those who previously stuttered in reading, memorizing and reviewing the teaching material that had been delivered by the teacher then they became more confident, and fluent. besides that they also have a strong enough memory.